Thermal management of an advanced aircraft actuation system - Goh, Chin Kung (2018)
The move in the aerospace industry towards More Electric Aircraft (MEA) resulted in an increased interest in using electric motors and power electronics in flight control surface application. As temperature limits impose power constraints on both electric machines and power electronics, cooling and thermal management of the electric motor and the electronics are essential. The purpose of the thesis is to extend the knowledge about cooling power electronics through natural convection heat transfer. More specifically, the design and optimisation of extended surface (fin) to enhance natural convection heat transfer. Experimental work carried out on a b-shaped heat sink and a straight base plate heat sink, both with staggered fins, is presented. The experimental work provided the empirical data used to validate numerical model predictions. Two numerical techniques were employed in this research: thermal resistance network and Computational Fluid Dynamics (CFD). Once validated, the numerical techniques were used to generate designs of heat sink with different plate thickness and fin configurations in order to optimise the heat transfer. It's demonstrated in the thesis on how numerical techniques can be used to obtain information and visualisation of the cooling mechanism, air flow and temperature profile of heat sink with straight fins in staggered arrangement. In particular, heat plume phenomenon is found to play a significant role in natural convection heat transfer. With the insight into natural convection heat transfer provided by the numerical techniques, design optimisation was performed to improve the thermal performance of the heat sink.